2023
DOI: 10.2147/idr.s402278
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Antibiotic Resistance Characteristics of Bacteria Isolated from Blood Culture in a Teaching Hospital in Vietnam During 2014–2021

Abstract: Purpose Studies on the epidemiology of bloodstream infection (BSI) and antimicrobial resistance (AMR) are limited in Vietnam. Thus, the present study aimed to elucidate the epidemiology of BSI and AMR of BSI-causing bacteria in Vietnam. Methods Data regarding blood cultures from 2014 to 2021 were collected and analyzed using the chi-square test, Cochran–Armitage test, and binomial logistic regression model. Results Overall, 2405 (14.15%) bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
3
6
1
Order By: Relevance
“…Furthermore, the VINARES report from 2016–2017 revealed that E. coli strains isolated from blood and cerebrospinal fluid samples exhibited a carbapenem resistance rate of 8%, surpassing the resistance rate observed in this study. 16 , 20 In addition, a comprehensive analysis (focusing on bloodstream infections (BSIs)) conducted from 2017 to 2019 showed that E. coli resistance to carbapenems ranged from 0.1% to 0.2%, which is consistent with the results of the present study, consistently low rates of E. coli resistance to carbapenems. 22 Meanwhile, the resistance rates for piperacillin/tazobactam and cefoperazone/sulbactam remain at a low level, which indicates that these antibacterial medications containing enzyme inhibitors could still be viable treatment options for E. coli -caused bloodstream infections.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the VINARES report from 2016–2017 revealed that E. coli strains isolated from blood and cerebrospinal fluid samples exhibited a carbapenem resistance rate of 8%, surpassing the resistance rate observed in this study. 16 , 20 In addition, a comprehensive analysis (focusing on bloodstream infections (BSIs)) conducted from 2017 to 2019 showed that E. coli resistance to carbapenems ranged from 0.1% to 0.2%, which is consistent with the results of the present study, consistently low rates of E. coli resistance to carbapenems. 22 Meanwhile, the resistance rates for piperacillin/tazobactam and cefoperazone/sulbactam remain at a low level, which indicates that these antibacterial medications containing enzyme inhibitors could still be viable treatment options for E. coli -caused bloodstream infections.…”
Section: Discussionsupporting
confidence: 90%
“…This resistance rate closely aligns with the 56.5% reported by Wang et al, 32 underscoring the consistent and concerning trend of carbapenem resistance in Acinetobacter baumannii strains, 32 furthermore, it is noteworthy that the rate of carbapenem resistance observed in our investigation of A. baumannii bloodstream infections (BSIs) was comparatively lower than that reported in BSI studies conducted in other geographical regions. 16 , 20 , 22 In contrast, P. aeruginosa exhibits a lower resistance rate than A. baumannii , with carbapenem resistance at only approximately 5%. Data obtained from a comprehensive study conducted at a tertiary care hospital in Beijing unveiled a concerning resistance rate of 27.8% among P. aeruginosa strains towards carbapenem antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies focus on various aspects of AMR occurrence and "frequency" in the health system, society, and the environment. Three studies conducted in Cameroon, Morocco, and Vietnam showed Enterobacteriaceae as the most frequently isolated microorganisms, followed by S. aureus, as we determined, but Camara N. and Haeeb A. determined an opposite situation in Tanzania and Saudi Arabia (2,9,27,28,29). When analyzing isolates according to the source (biosubstrate), studies focusing on uropathogens showed that E. coli is the most frequent uropathogen followed by K. pneumoniae (in Ethiopia and USA), compared to 2 studies from Romania showing 2 distinct situations -one study showed a similar situation as in Ethiopia, and the second one showed a distinct situation -with P. aeruginosa on the first place similar to the one in Mexico (14, 25, 30 31, 32).…”
Section: Discussionmentioning
confidence: 45%
“…It should be noted that antimicrobial-resistant pathogens not only cause an increased number of deaths (mortality caused by multi-drug resistant (MDR) P. aeruginosa reaches up to 61% of cases, and pan-drug resistant (PDR) K. pneumoniaemaximum 71%) and disability, but also additional costs for hospitalization, treatment, and recovery, which cannot be accurately calculated (5,8,9). Specialists from various countries have concluded that the economic status of a country significantly influences the impact of AMR on the population, largely due to investment size in surveillance systems for antimicrobial resistance of microorganisms, but also to the presence and quality of alternative resources that can be used to fight infections (10).…”
Section: Introductionmentioning
confidence: 99%
“…Isolates were nonsusceptible to ≥1 agent in ≥3 antimicrobial classes were considered multi-drug resistant (MDR). 27 , 28 The tested antimicrobials and their detection concentration are mentioned in Table S1 .…”
Section: Methodsmentioning
confidence: 99%